2000
DOI: 10.1128/aac.44.3.771-772.2000
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Ultrasound Enhances the Killing of Escherichia coli Biofilms by Aminoglycoside Antibiotics In Vivo

Abstract: Escherichia coli biofilms on two polyethylene disks were implanted subcutaneously into rabbits receiving systemic gentamicin. Ultrasound was applied for 24 h to one disk. Both disks were removed, and viable bacteria were counted. Pulsed ultrasound significantly reduced bacterial viability below that of nontreated biofilms without damage to the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 5 publications
3
92
0
Order By: Relevance
“…No significant changes were incurred to the Pseudomonas aeruginosa biofilm matrix or its bacterial cells in the absence of gentamicin [88]. The viability of Escherichia coli biofilms has also been significantly reduced in vivo using pulsed low frequency ultrasound (25% duty, power intensity 500 mW/cm 2 for a treatment period of 24 or 48 h) in combination with gentamicin but these effects were not reproducible against Pseudomonas aeruginosa biofilms [89][90][91]. In 2005, Ensing et al [92] also demonstrated greater than 50% reductions in the viability of Escherichia coli biofilms by combining pulsed ultrasound treatment (24-48 kHz, power intensity 500 mW/cm 2 ) with gentamicin.…”
Section: Biofilm Prevention and Control Using Acoustic Energymentioning
confidence: 99%
“…No significant changes were incurred to the Pseudomonas aeruginosa biofilm matrix or its bacterial cells in the absence of gentamicin [88]. The viability of Escherichia coli biofilms has also been significantly reduced in vivo using pulsed low frequency ultrasound (25% duty, power intensity 500 mW/cm 2 for a treatment period of 24 or 48 h) in combination with gentamicin but these effects were not reproducible against Pseudomonas aeruginosa biofilms [89][90][91]. In 2005, Ensing et al [92] also demonstrated greater than 50% reductions in the viability of Escherichia coli biofilms by combining pulsed ultrasound treatment (24-48 kHz, power intensity 500 mW/cm 2 ) with gentamicin.…”
Section: Biofilm Prevention and Control Using Acoustic Energymentioning
confidence: 99%
“…Pulsed US applied for 48 hours with gentamicin was effective in eliminating E. coli infections [204], but was less effective against P. aeruginosa [205]. Vancomycin combined with US was somewhat effective against S. epidermidis infections in the same rabbit model [206].…”
Section: Antibacterialmentioning
confidence: 99%
“…To this end, our research group is pursuing alternative treatments. Previous in vivo experiments showed that gentamicin combined with 24 h of ultrasonic treatment resulted in the enhanced reduction of viable bacteria in Escherichia coli biofilms (5,6). In this article, we report the successful use of ultrasound in vivo when the treatment of Escherichia coli biofilms was extended to 48 h, and the failure of such therapy to reduce viable bacteria in Pseudomonas aeruginosa biofilms.…”
Section: Introductionmentioning
confidence: 86%
“…The biofilms were grown for 24 h on polyethylene disks as reported previously (5,6). E. coli ATCC 10798 and P. aeruginosa ATCC 27853 used in these experiments had planktonic MIC values of 6 and 3 ug/mL respectively.…”
Section: Methodsmentioning
confidence: 99%